1999
DOI: 10.1038/sj.bmt.1701605
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary enterovirus infections in stem cell transplant recipients

Abstract: Summary:In recent years, it has been recognised that the community respiratory viruses are a frequent cause of upper and lower respiratory tract infections in immunocompromised hosts such as bone marrow transplant recipients. By contrast, infections by non-polio enteroviruses have rarely been reported after stem cell transplantation. We present four cases of acute respiratory illness with enterovirus isolated as the sole pathogen from bronchoalveolar lavage. All four patients developed pneumonia and three died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 9 publications
(9 reference statements)
2
26
0
Order By: Relevance
“…However, EVs have been reported as a cause of pneumonia in bone marrow transplant patients. Thus, testing of respiratory samples may be indicated (4). One could also argue that since the only therapy available on compassionate plea for EV or rhinovirus is pleconaril, the distinction between the two groups may not be clinically relevant (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, EVs have been reported as a cause of pneumonia in bone marrow transplant patients. Thus, testing of respiratory samples may be indicated (4). One could also argue that since the only therapy available on compassionate plea for EV or rhinovirus is pleconaril, the distinction between the two groups may not be clinically relevant (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, enteric viruses such as adenovirus, rotavirus and enteroviruses have been reported to cause serious infection in these patients. [1][2][3][4][5][6] The role of enteric viruses has been prospectively investigated in only a few studies to date. 7,8 Previous studies have indicated a high incidence of viral gastro-enteritis in bone marrow transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The role of cell-mediated immunity in the genesis of enteroviral infections is not clear. It is predominantly observed in patients with defects in the humoral arm of the immune system manifesting often as meningoencephalitis.…”
Section: Disseminated Echovirus and Othermentioning
confidence: 99%
See 1 more Smart Citation
“…Life-threatening enterovirus infections may occur, especially in at-risk individuals such as immunocompromised patients. Recently, bone marrow transplantation patients have been found to be infected with enteroviruses, resulting in serious complications such as pneumonia (6,19). The relatively immunodeficient neonate is also at risk for severe enterovirus infections, resulting in serious febrile illnesses in the first weeks of life (23,26).…”
mentioning
confidence: 99%